A6.28 The role of Plexin-D1/Semaphorin 3E pathway in the dysregulation of vascular tone control in systemic sclerosis (SSc). (13th February 2015) - Mazzotta, C; Romano, E; Bruni, C; Manetti, M; Lepri, G; Bellando-Randone, S; Blagojevic, J; Ibba-Manneschi, L; Matucci-Cerinic, M; Guiducci, S
Abstract : Background and objectives: The vascular and nervous systems have several anatomic and molecular mechanism similarities. Emerging evidence suggests that proteins involved in transmitting axonal guidance cues, including class III semaphorin families, also play a critical role in blood vessel guidance during physiological and pathological vessel development. Sema3E is a natural antiangiogenic molecule that causes filopodial retraction in endothelial cells, inhibiting cell adhesion by disrupting integrin-mediated adhesive structures. The aim of the present study was to investigate if Plexin-D1/Sema3E axis could be involved in the dysregulation of vascular tone control (RF) in SSc. Materials and methods: Sema3E levels were measured by quantitative colorimetric sandwich ELISA in serum samples from 45 subjects with primary Raynaud's phenomenon (pRP), 48 SSc patients and 48 age- and sex-matched healthy controls. Western blot was used to evaluate Plexin-D1/Sema3E axis in human SSc and healthy dermal microvascular endothelial cells (SSc-MVEC and H-MVEC, respectively) at basal condition, and after stimulation with recombinant human vascular endothelial growth factor (VEGF), SSc and healthy sera (both n = 3). Immunofluorescence staining on skin sections from 14 SSc patients and 12 healthy subjects was performed in order to evaluate Sema3E and Plexin-D1 expression. Results: Serum Sema3E levels were significantly higher both in pRP subjects and SSc patients than in sera controls. In SSc, Sema3E levels were significantly increased in patients with early nailfold videocapillascopy pattern (NVC) compared to active/late pattern and pRP, and in patients without ulcers compared to those with digital ulcers. SSc-MVEC showed higher levels of phosphorylated Plexin-D1 and Sema3E expression compared with H-MVEC, and stimulation with SSc sera increased the expression of phosphorylated Plexin-D1 and Sema3E in H-MVEC. In SSc, Sema3E expression was increased in the dermis, particularly in the vascular endothelium. Conclusions: Our findings suggest that Plexin-D1/Sema3E axis is triggered in SSc and may have a role in the dysregulation of vascular tone control by inducing neuro-vascular mechanism alterations clinically evident in particular in the early disease phases.